Acute Effect of the Compression Technique on the Electromyographic Activity of the Masticatory Muscles and Mouth Opening in Subjects with Active Myofascial Trigger Points - Michał Ginszt; Grzegorz Zieliński; Marcin Berger; Jacek Szkutnik; Magdalena Bakalczuk; Piotr Majcher (Applied Sciences, 2020)
Active myofascial trigger points (MTrPs) in masticatory muscles are associated with a reduced range of motion and muscle weakness within the stomatognathic system. However, it is hard to identify the most effective treatment technique for disorders associated with MTrPs. The objective of this study was to analyze the acute effect of the compression technique (CT) on active maximal mouth opening (MMO) and electromyographic activity of the masseter (MM) and temporalis anterior (TA) muscles in subjects with active myofascial trigger points in the MM muscles. The study group comprised 26 women (mean age 22 ± 2) with bilateral active myofascial trigger points (MTrPs) in the MM. The control group comprised 26 healthy women (mean age 22 ± 1) without the presence of MTrPs in the MM. Masticatory muscle activity was recorded in two conditions (during resting mandibular position and maximum voluntary clenching) before and after the application of the CT to the MTrPs in MM. After the CT application, a significant decrease in resting activity (3.09 μV vs. 2.37 μV, p = 0.006) and a significant increase in clenching activity (110.20 μV vs. 139.06 μV, p = 0.014) within the MM muscles were observed in the study group, which was not observed within TA muscles. Controls showed significantly higher active MMO values compared to the study group before CT (50.42 mm vs. 46.31 mm, p = 0.024). The differences between the study group after CT and controls, as well as among the study group before and after CT did not reach the assumed level of significance in terms of active MMO. The compression technique appears to be effective in the improvement of the active maximal mouth opening and gives significant acute effects on bioelectric masticatory muscle activity. Therefore, CT seems to be effective in MTrPs rehabilitation within the stomatognathic system.